The Effect of Tahajjud on Students’ Stress Mediated By Personality Types - Ogmun, Maryam; Susiyadi, Susiyadi; Kusumawinakhyu, Titik; Safithri, Abidah; Almanfaluthi, Muhammad; Widodo, Stefani (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2025)
New Medical students experience massive adaptation from school to university level. Some of them experience adaptation difficulties, even stress. Religious activities are believed to provide serenity, stress reduction, and confidence enhancement, but the magnitude needs to be clarified. It is also postulated that different personality types (phlegmatic, sanguine, choleric, and melancholic) have different stress-coping mechanisms. We aim to investigate the impact of tahajjud on stress levels and how personality type reacts to these changes. Seventy-four first-year medical students evaluated their stress levels with Kessler’s Psychological Distress Scale (KPDS) for the student before and after three months of continuous daily exposure with tahajjud and dhikr. The students were also stratified based on the personality types based on the Hippocrates-Galenus classification. We found that tahajjud and dhikr significantly reduce student’s stress levels (Wilcoxon test P<0.001). Melancholy types take huge advantages from these religious activities regarding stress reduction compared to others (ANOVA, p<0.018). Regular Tahajjud and dhikr could be recommended programs in Muslim institutions.